METODE KRITIK TEKS DALAM TEMBANG SINOM (Implementasi Keilmuan di Bidang Linguistik) - Novena Ade Fredyarini Soedjiwo (Widya Balina, 2019)
Abstract Language as a communication tool is very important in human life. Language is used to preserve and preserve culture, linguists need to implement their knowledge in the application of methods and theories.Cultural traditions need to be preserved through the fields of tourism, education, and social culture. Writer is interested in preserving the manuscript. A lot of manuscripts that hereditary experienced changes in the text. The writer wants to know the form of Tembang Sinom text which experiences some text changes using the text critique method. In addition, writer wants to apply methods and theories to the text of the Tembang Sinom. The data comes from one song about puberty. Data were analyzed with a qualitative descriptive analytical approach. The results of form Tembang Sinom text in puberty theme, it has an approach to the original which has three derivatives, and the author is affected by the situation at the time of singing Tembang Sinom. It changed in its derivatives. But it does not come out of the theme of puberty and still contains good advice.